Adaptive neuro-fuzzy inference system coupled with shuffled frog leaping algorithm for predicting river streamflow time series - Mohammadi B.; Linh N.T.T.; Pham Q.B.; Ahmed A.N.; Vojtekov J.; Guan Y.; Abba S.I.; El-Shafie A. (Taylor and Francis Ltd., 2023)
Catchments; Forecasting; Fuzzy neural networks; Fuzzy systems; Inference engines; Rivers; Stream flow; Water management; Adaptive neuro-fuzzy inference system; Forecasting accuracy; Forecasting modeling; Model inputs; Prediction accuracy; Runoff forecasting; Shuffled frog leaping algorithm (SFLA); Water resources systems; Fuzzy inference; accuracy assessment; algorithm; fuzzy mathematics; prediction; river flow; runoff; streamflow; time series; Anura